An optimal loss-reduction control strategy for MMC considering capacitor voltage ripple suppression - FANG Dongping; QIU Yang; CUI Jindong; FEI Lisong; TANG Fangjie; ZHAO Jiancheng (Zhejiang dianli, 2025)
Existing capacitor voltage ripple suppression methods primarily rely on second-harmonic circulating current injection （SHCCI）. However， these methods often increase valve losses in modular multilevel converters （MMCs） ， degrading operational efficiency and reliability. To address this challenge， this paper first analyzes the capacitor voltage ripple characteristics of MMCs under optimal SHCCI and reveals the additional converter valve losses incurred by ripple suppression. For medium- and low-voltage MMCs employing carrier phase shift pulse width modulation （CPS-PWM）， a loss-reduction control strategy is proposed that explicitly considers capacitor voltage ripple suppression. Based on the optimization objectives and constraints of capacitor voltage ripple and valve loss， the bridge arm current is optimally controlled to eliminate the valve loss increment induced by ripple suppression while maintaining ripple suppression performance. Finally， a comparative analysis under multiple operating conditions is performed in MATLAB/Simulink to validate the accuracy of the valve loss characteristic analysis and the effectiveness of the proposed control strategy.